Assessment of the EPA-SWMM Software for Urban Stormwater Management Manual (MSMA) Requirement - Intan Mastura Bt. Mohamad Azmi, Intan Mastura (Universiti Teknologi Petronas, 2010)
The purposes of this project are to identify and investigate the assessment of the EPA Storm Water Management Model (EPA SWMM) for urban stormwater management in order to meet the MSMA requirement and make a comparison with manual calculation in term of the physical quantity.